BALON JOURNAL PENLIT, JIWA Anak TKW 2021 - Eddy Wasito; Crismantoro Budisaputro (PT.Mantaya Idea Batara, 2022)
This research is a field study with the title Study on the Development of the Social Soul of Women's Child Labor using qualitative research approaches and inductive methods. The expected purpose of the research is to find out how the Development of Social Soul of Women child Labor Children and parenting patterns in Joho Village, Merchandise Subdistrict, Madiun Regency. The problem in this study is how is the development of Social Soul and childcare patterns of Women Workers in Joho Village, Merchandise Subdistrict, Madiun Regency?. Research data will be extracted from primary data sources and pseudo-data sources. While the methods used to collect data are methods of observation, interview and dukumentation. Based on the results of data collection, data analysis and discussion showed that the development of the Social Soul of Women's Child Labor is different from children who are always accompanied by their mothers. Childcare is better done by parents because the child's Social Soul Development will be able to develop more optimally in accordance with the rhythm of mental development and will lead the child to better growth, the child can be more independent and can socialize with the environment and be more responsible. While the development of the Social Soul of Women's Child Labor in general experiences psychological social barriers that will not interfere with their developmental tasks.